2020
DOI: 10.3390/nu12092754
|View full text |Cite
|
Sign up to set email alerts
|

Cocoa-Rich Chocolate and Quality of Life in Postmenopausal Women: A Randomized Clinical Trial

Abstract: Menopause has a negative impact on quality of life (QoL). The aim of the present study was to analyse the effect on QoL of adding 10 g per day of chocolate with a high concentration of cocoa (99%) to the habitual diet, for 6 months, in a sample of postmenopausal women. Postmenopausal women (n = 140) aged 50–64 years were randomised to either an addition of 10 g per day of cocoa-rich chocolate to their usual diet or no supplement addition. All variables were measured at baseline and after six months of interven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
0
1
0
Order By: Relevance
“…Our present POMS2 results suggest that in middle-aged women, the consumption of flavanol-rich cacao extract reduces negative mood features, such as depression, fatigue, and anxiety, and improves the positive mood features vigor and activity. Gracia-Yu et al reported that an additional daily consumption of 10 g of cocoa-rich chocolate by postmenopausal women could have a slight impact on their perception of the state of their health, although those authors noted that this was without modifications of the women's health-related QoL or the dimensions that compose it [23]. One of our earlier studies demonstrated that in both middle-aged women and middle-aged men, a daily consumption of dark chocolate increased QoL scores [24].…”
Section: Discussionmentioning
confidence: 99%
“…Our present POMS2 results suggest that in middle-aged women, the consumption of flavanol-rich cacao extract reduces negative mood features, such as depression, fatigue, and anxiety, and improves the positive mood features vigor and activity. Gracia-Yu et al reported that an additional daily consumption of 10 g of cocoa-rich chocolate by postmenopausal women could have a slight impact on their perception of the state of their health, although those authors noted that this was without modifications of the women's health-related QoL or the dimensions that compose it [23]. One of our earlier studies demonstrated that in both middle-aged women and middle-aged men, a daily consumption of dark chocolate increased QoL scores [24].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, an improvement was observed in mobility problems and pain/discomfort [ 46 ]. However, another clinical trial states that 10 g of chocolate rich in cocoa (99%) per day in postmenopausal women, for 6 months, could have a slight impact on the perception of their health, although without modifying the health-related quality of life [ 47 ]. There are also some studies that mention a better quality of life in patients when ingesting polyphenols, but without specifically measuring it, but rather as a secondary consequence.…”
Section: Discussionmentioning
confidence: 99%